Cormac McCarthy : new directions - Lilley, James D. (James David), 1971- (University of New Mexico Press, 2002)
Critics have been quick to address Cormac McCarthy's indebtedness to southern literature, Christianity, and existential thought, but the essays in this collection are among the first to tackle such issues as gender and race in McCarthy's work.